Dato' Hussamuddin Yaacub / Hartini Jubidi and Noor Faezah Hasan - Jubidi, Hartini; Hasan, Noor Faezah (2011)
Dato' Hussamuddin bin Yaacub is a Managing Director for Kumpulan Karangkraf which is known as entrepreneur that success in control the publishing and printing sector in this country. Name of Kumpulan Karangkraf has been changed to the Kumpulan Media Karangkraf which has more desire to contribute larger and significant in the development of publishing and printing industry nationwide. Over three decades ago, this company began only with a book that title " Sorotan Sejarah Melayu ", writing by Johan Jaafar and followed by a weekly magazine for children. Now, Kumpulan Media Karangkraf published 28 magazines and one newspaper, Sinar Harian with eight edition of the state. Dato' Hussammudin bin Yaacub was still the most important person that has responsibilities to publish more variety types of printed materials. He also hopes that this opportunity can increase the number of readers in Malaysia.